The clinical potential of 1,5-anhydroglucitol as biomarker in diabetes mellitus - Xu, Haiying; Chen, Renyin; Hou, Xiaoli; Li, Na; Han, Yanwei; Ji, Shaoping (Frontiers in Endocrinology, 2024)
A crucial measure of diabetes management is to monitor blood glucose, which often requires continuous blood collection, leading to economic burden and discomfort.Blood glucose and glycated hemoglobin A1c serve as traditional indicators of glucose monitoring. But now glycated albumin, fructosamine, and 1,5-anhydroglucitol (1,5-AG) have been gaining more attention. 1,5-AG is a chemically stable monosaccharide that exists in the human body. Its serum concentration remains stable when blood glucose levels are normal. However, it decreases when blood glucose exceeds the renal glucose threshold. Studies have shown that 1.5-AG reflects blood glucose changes in 1 to 2 weeks; therefore, decreased levels of serum 1,5-AG can serve as a clinical indicator of short-term blood glucose disturbances. Recent studies have shown that 1,5-AG can be used not only for the screening and managing of diabetes but also for predicting diabetes-related adverse events and islet β cell function in prediabetic patients. In addition, saliva 1,5-AG demonstrates potential value in the screening and diagnosis of diabetes. This review focuses on the biological characteristics, detection methods, and clinical application of 1,5-AG to promote understanding and applicable research of 1,5-AG in the future.